Of buds and bits: a meta-QTL study identifies stable QTL for berry quality and yield traits in cranberry mapping populations (Vaccinium macrocarpon Ait.) - Maule, Andrew F.; Loarca, Jenyne; Diaz-Garcia, Luis; Lopez-Moreno, Hector; Johnson-Cicalese, Jennifer; Vorsa, Nicholi; Iorizzo, Massimo; Neyhart, Jeffrey L.; Zalapa, Juan E. (Frontiers in Plant Science, 2024)
For nearly two centuries, cranberry (Vaccinium macrocarpon Ait.) breeders have improved fruit quality and yield by selecting traits on fruiting stems, termed 'reproductive uprights'. Crop improvement is accelerating rapidly in contemporary breeding programs due to modern genetic tools and high throughput phenotyping methods, improving selection efficiency and accuracy. We conducted genotypic evaluation on 29 primary traits encompassing fruit quality, yield, and chemical composition in two full-sib cranberry breeding populations -CNJ02 (n=168) and CNJ04 (n=67)over three years. Genetic characterization was further performed on 11 secondary traits derived from these primary traits. For CNJ02, 170 major quantitative trait loci (QTL; R 2 ≥ 0.10) were found with interval mapping, 150 major QTL were found with model mapping, and 9 QTL were found to be stable across multiple years. In CNJ04, 69 major QTL were found with interval mapping, 81 major QTL were found with model mapping, and 4 QTL were found to be stable across multiple years. MetaQTL represent stable genomic regions consistent across multiple years, populations, studies, or traits. Seven multi-trait metaQTL were found in CNJ02, one in CNJ04, and one in the combined analysis of both populations. A total of 22 metaQTL were identified in cross-study, cross-population analyses using digital traits for berry shape and size (8 metaQTL), digital images for berry color (2 metaQTL), and three-study cross-analyses (12 metaQTL). Together, these metaQTL anchor high- throughput fruit quality phenotyping techniques to traditional phenotyping methods, validating stateof-the-art methods in cranberry phenotyping that will improve breeding accuracy, efficiency, and genetic gain in this globally significant fruit crop.